2022
DOI: 10.3390/cancers14215355
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Malignant Lymph Nodes Using a Novel Scoring System Based on Multi-Endobronchial Ultrasound Features

Abstract: Endobronchial ultrasound (EBUS) features with B-, power/color Doppler, and elastography modes help differentiate between benign and malignant lymph nodes (MLNs) during transbronchial needle aspiration (TBNA); however, only few studies have assessed them simultaneously. We evaluated the diagnostic accuracy of each EBUS feature and aimed to establish a scoring system to predict MLNs. EBUS features of consecutive patients and final diagnosis per lymph node (LN) were examined retrospectively. In total, 594 LNs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In predicting malignant lymph nodes, our 5 EBUS features nomogram consisted of long-axis, short-axis, echogenicity, fusion, and CHS. The optimal AUC value for this nomogram was 0.905 which was better than the Canada LN score (AUC = 0.72) and eight EBUS features (AUC = 0.857) [ 13 , 14 ] and also had a good predictive efficacy in predicting various cancer cell types. In predicting malignancy outcomes of EBUS-TBNA postoperative negative lymph nodes, our 3 EBUS features nomogram consisted of long-axis, echogenicity, and CHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In predicting malignant lymph nodes, our 5 EBUS features nomogram consisted of long-axis, short-axis, echogenicity, fusion, and CHS. The optimal AUC value for this nomogram was 0.905 which was better than the Canada LN score (AUC = 0.72) and eight EBUS features (AUC = 0.857) [ 13 , 14 ] and also had a good predictive efficacy in predicting various cancer cell types. In predicting malignancy outcomes of EBUS-TBNA postoperative negative lymph nodes, our 3 EBUS features nomogram consisted of long-axis, echogenicity, and CHS.…”
Section: Discussionmentioning
confidence: 99%
“…A distinct margin, round shape, heterogeneous echogenicity, and coagulation necrosis sign were independent predictors of metastasis in multivariate analysis, each with an OR of 3.05, 3.1, 1.96, and 5.64. Morishita et al reported on multi-EBUS features [ 14 ]. A total of 597 lymph nodes were evaluated retrospectively from 302 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that used blood flow grade instead of vascular distribution to predict metastasis found that it was not significant independent predictors of LNs metastasis. [ 21 , 32 ] This reason might be that blood flow grade was more affected by external factors, such as pulsation of great vessels and respiratory movement. [ 14 ] The elastography had the accuracy of 77.64%, which was a useful EBUS modality to detect the tissue stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, most studies investigating the performance characteristics of B-mode endosonography findings in predicting malignant ILN involvement have not included calcifications in the analysis. [13][14][15][16][17][18][19][20][21][22] Moreover, previous studies examining the predictive value of ILN calcifications were conducted in countries with a high prevalence of tuberculosis, did not differentiate between macrocalcifications and microcalcifications, and reported a low prevalence of calcifications, limiting robust statistical analysis. [23][24][25][26] associated with a high prevalence of malignancy and actionable driver mutations in the setting of lung cancer.…”
mentioning
confidence: 99%
“…Intrathoracic lymph node (ILN) calcifications have traditionally been attributed to prior granulomatous inflammatory conditions (eg, sarcoidosis) or infectious diseases (eg, tuberculosis, histoplasmosis). Consequently, most studies investigating the performance characteristics of B-mode endosonography findings in predicting malignant ILN involvement have not included calcifications in the analysis 13–22 . Moreover, previous studies examining the predictive value of ILN calcifications were conducted in countries with a high prevalence of tuberculosis, did not differentiate between macrocalcifications and microcalcifications, and reported a low prevalence of calcifications, limiting robust statistical analysis 23–26 …”
mentioning
confidence: 99%